Look East Policy: The Case of Zimbabwe–China Political and Economic Relations Since 2000 - Ojakorotu, Victor; Kamidza, Rumbidzai (SAGE Publications Inc., 2021)
This article maps the evolution of Zimbabwe’s Look East Policy (LEP) and specifically the bilateral relationship with China through the lens of Zimbabwe’s domestic politics. It argues that political elite in Zimbabwe has a vested interest in a close economic and political relationship with China at the cost of the interests of the people of Zimbabwe. The author establishes that Zimbabwe’s LEP was intended to respond to the economic sanctions imposed on it by Western nations. From the descriptive account of the LEP provided in the article, it appears that the LEP has been successful in doing that by having a broad-based economic and political relationship with China. The author further critiques the impact of Chinese investment in Zimbabwe as detrimental to the interests of the people.